Meta-Sex 94 : Identity, Body and Sexuality. - Katz-Freiman, Tami; El-Or, Tamar; Bat Yam Museum, Bat Yam (Ein-Harod : Mishkan Le'omanut - Museum of Art, 1994)
Barzilay, Tiranit ; Betzer-Shapira, Anat ; Cabessa, Miriam ; Eilat, Galit ; Friedmann, Max ; Hashahar Cohen, Ayelet ; Hod, Nir ; Levin, Merilou ; Littman-Cohen, Ariane ; Lulu Lin, Hila ; Masel, Tamara ; Mayslits-Kassif, Ganit ; Shamir, Michal ; Shemesh, Meira ; Zahor, Anat
Meta-Sex 94 : Identity, Body and Sexuality, Mishkan Le'omanut - Museum of Art, Ein-Harod, June - July 1994 ; Bat Yam Museum, Bat Yam, October - November 1994
boek